ACL Reconstruction Patients Have Increased Risk of Knee Arthroplasty at 15 Years of Follow-up: Data from the Norwegian Knee Ligament Register and the Norwegian Arthroplasty Register from 2004 to 2020. Issue 2 (21st April 2022) - Visnes, Håvard; Gifstad, Tone; Persson, Andreas; Lygre, Stein Håkon Låstad; Engebretsen, Lars; Drogset, Jon Olav; Furnes, Ove
Abstract : Background: Anterior cruciate ligament (ACL) injury is considered a risk factor for osteoarthritis. The primary aim of the present study was to investigate the cumulative risk of, and risk factors associated with, a subsequent knee arthroplasty after an ACL reconstruction at up to 15 years of follow-up. The secondary aim was to compare the relative risk of knee arthroplasty after ACL reconstruction compared with that in the general population. Methods: Data were analyzed by combining data from 2 national registries, the Norwegian Knee Ligament Register and the Norwegian Arthroplasty Register. The cumulative risk of knee arthroplasty after undergoing ACL reconstruction was calculated as 1 minus the corresponding Kaplan-Meier estimate, and possible risk factors for knee arthroplasty after ACL reconstruction were assessed in a Cox regression model with hazard ratios (HRs) as estimated effect measurements. The relative risk of knee arthroplasty for patients managed with ACL reconstruction as compared with that in the general population was calculated in stratified age groups. Results: From the study population of 27, 122 knees, 115 knees underwent knee arthroplasty. We found a 1.1% (95% confidence interval [CI], 0.9 to 1.4) cumulative risk of knee arthroplasty 15 years after ACL reconstruction. Deep cartilage injury, ICRS (International Cartilage Repair Society) grade 3 to 4 (HR, 4.8; 95% CI, 3.1 to 7.6), revision of the ACL (HR, 3.9; 95% CI, 2.2 to 7.1), and a 2-year postoperative KOOS Sport/Recreation subscore of <44 (HR, 3.1; 95% CI, 1.5 to 6.2) were important risk factors for knee arthroplasty. We found a higher risk of knee arthroplasty at the age of 30 to 39 years after a previous ACL reconstruction as compared with the general population (relative risk, 3.3; 95% CI, 1.6 to 6.7). Conclusions: Fifteen years after an ACL reconstruction, the overall cumulative risk of knee arthroplasty was 1.1%. Cartilage injury at the time of ACL reconstruction, revision ACL reconstruction, and a KOOS Sport/Recreation subscore of <44 (at 2 years postoperatively) were major risk factors for subsequent knee arthroplasty. We found a 3.3-times higher risk of knee arthroplasty at the age of 30 to 39 years after a previous ACL reconstruction as compared with that in the general population. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.